2017
DOI: 10.5327/z1677-606220172193
|View full text |Cite
|
Sign up to set email alerts
|

Características fisiográficas de sub-bacias do Médio e Alto Rio Teles Pires, Mato Grosso

Abstract: Características fisiográficas de bacias hidrográficas são todos os dados que podem ser extraídos de mapas, fotografias aéreas e imagens de satélites com auxílio de sistemas de informações geográficas. Essas características possuem importância expressiva para a modelagem hidrológica, a regionalização de vazões e a gestão de recursos hídricos. Objetivou-se determinar as características fisiográficas de cinco sub-bacias nas regiões do Médio e Alto Rio Teles Pires, localizadas na região Amazônica do estado de Mato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…As independent variables, we used the following physiographic traits of the sub-basins: drainage area (AD, km 2 ), perimeter (P, km), total watercourse length (LT, km), axial length (L, km), basin mean elevation (Alt., meters), and basin mean slope (D, m/m). These characteristics were obtained following the procedures described by Villela and Mattos (1975) and by Wenzel et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…As independent variables, we used the following physiographic traits of the sub-basins: drainage area (AD, km 2 ), perimeter (P, km), total watercourse length (LT, km), axial length (L, km), basin mean elevation (Alt., meters), and basin mean slope (D, m/m). These characteristics were obtained following the procedures described by Villela and Mattos (1975) and by Wenzel et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…the region is relatively flat and consequently there are no great variations between the altitudes and their respective drainage areas (WENZEL et al, 2017). According to the authors, the average altitudes calculated for the sub-basins 17380000, 17300000, 17280000, 17210000 and 17200000 were 371 m, 412 m, 421 m, 455.6 m and 472 m, respectively.…”
Section: /13mentioning
confidence: 98%
“…When analyzing the average slopes of the drainage areas of the Teles Pires River, Wenzel et al (2017) found that most of the sub-basin slopes vary from 0 to 1%, concluding that they fall into flat relief. Other information related to the physiographic characteristics of the sub-basins used in this study can be consulted in the research of these authors.…”
Section: /13mentioning
confidence: 99%
“…In natural rivers, flow estimation is complex, as the cross-section can be irregular, in which case it is recommended to measure the flow in loco [12]. The main variables obtained in loco are the speed and water level and, in turn, the flow, regardless of the method.…”
Section: Introductionmentioning
confidence: 99%